(untitled) (Journal of Social Sciences Review, 2023)
The right to information is a powerful tool of good governance without which Transparency and Accountability remain a mere aspiration and an allegory. The basic purpose of this study is to analyze the importance of RTI in general and to provide an overview of the introduction of this basic human right in the conflicts-affected province of Khyber Pakhtunkhwa of Pakistan in particular. RTI ACT of 2013 in KP was the first serious effort of the PTI provincial government in the country. For accomplishing this task, qualitative methodology with primary and secondary sources as an instrument for collecting data has been employed. Key informant interviews were conducted with members of the Provincial Assembly of KP and officials in the RTI Commission to record their opinion about RTI. The piece of study has highlighted the brief history of the efforts of introducing this law in Pakistan and analyzed the features, mechanism, and success extent of the RTI Act 2013 in Khyber Pakhtunkhwa. The paper concludes that the Act was highly respected throughout the country, as it was ranked 3rd in all global RTI Acts as it met basic international requirements like clearly defining and enumerating information and exemption from disclosure.